The development of molecular genetics concept test for senior high school students using Rasch analysis - Indah Juwita Sari; Pongprapan Pongsophon; Wanwipa Vongsangnak; Pattamaporn Pimthong; Sasithep Pitiporntapin (Institute of Advanced Engineering and Science, 2022)
Developing a high-quality test item requires substantial time and effort. A well-developed item bank is conducted using rigorous development and validation procedures. This study aimed to describe the development process of molecular genetics concept test (MGCT) for senior high school students using Rasch analysis under Berkeley evaluation and assessment research (BEAR) assessment system framework. The test consists of 50 multiple-choice items to assess conceptual understanding of molecular genetics concepts. The MGCT was developed based on curriculum analysis from the Indonesian ministry of education and culture and content-validated by three content experts comprising an expert in biology, an expert in bioinformatics, and an experienced Indonesian biology teacher in a senior high school. The MGCT was then piloted to 114 students who had taught the molecular genetics unit from a senior high school to conduct the empirical validation. The results from Rasch analysis showed that the MGCT is acceptable because all items have outfit and infit mean-square values in the acceptable range of 0.7 to 1.3 and the reliability is 0.43. So, the MGCT can be used to assess the understanding of the molecular genetics concept. However, several items were too difficult to discriminate the student ability. So, future studies need to develop more this MGCT to get a more appropriate instrument.